Removing Impediments to Sustainable Economic Development : The Case of Corruption - López Claros, Augusto (World Bank, Washington, DC, 2014)
This paper examines causes and consequences of corruption within the process of economic development. It starts by reviewing some of the factors that, over the past couple of decades, have transformed corruption from a subject on the sidelines of economic research to a central preoccupation of policy makers and donors in many countries. Drawing on a vast treasure trove of experiences and insights accumulated during the postwar period and reflected in a growing body of academic research, the paper analyzes many of the institutional mechanisms that sustain corruption and the impact of corruption on development. This paper argues that many forms of corruption stem from the distributional attributes of the state in its role as the economy's central agent of resource allocation. What is the impact of corruption on public finances and on the characteristics and performance of the private sector? What distortions does corruption introduce in the allocation of resources and in the relationships among economic agents in the marketplace? The paper also addresses the question of what can be done about corruption and discusses the role of economic policies in developing the right sorts of incentives and institutions to reduce the incidence of corruption. Particular attention is paid to business regulation, subsidies, the budget process, international conventions, and the role of new technologies. The paper concludes with some thoughts on the moral dimensions of corruption.